Media Pembelajaran Interaktif Berbasis Augmented Reality (AR) Untuk Meningkatkan Motivasi Belajar Anak - Nur Iksan; Djuniadi Djuniadi (Pusat Teknologi Informasi dan Pangkalan Data IAIN Syekh Nurjati Cirebon, 2017)
Based on observations related to the increasing interest of children to digital devices (smartphones, laptops), become an opportunity for teachers/educators to make ICT-based learning media with more interactive and interesting, thus improving motivation to learn children. One of the methods that can be used is Augmented Reality. Augmented Reality (AR) is a technology that can incorporate a 3D object into a real environment using a webcam medium. The advantages of this AR method is an interesting visual appearance because it can display 3D objects that seem to exist in the real environment. AR method also has advantages of the interactive side because it uses markers to display certain 3D objects that are pointed to the webcam. In addition, the application of concepts to be used can improve the reasoning power and imagination of learners.